2004
DOI: 10.1111/j.1442-9071.2004.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity‐associated mitochondrial DNA 5178 A/C polymorphism is associated with intraocular pressure in Japanese men

Abstract: Longevity-associated mitochondrial DNA 5178 A/C polymorphism may be associated with IOP in Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have found that both SBP and DBP were lower in non-drinkers with ND2-237Leu than in those with ND2-237Met (7), and that serum uric acid levels were lower in non-obese non-daily drinkers with ND2-237Leu than in those with ND2-237Met (11). Only among men with ND2-237Leu, habitual drinking was reportedly and positively associated with intraocular pressure (21). Therefore, abstaining from alcohol consumption, or at least avoiding daily alcohol consumption, is particularly recommended for ND2-237Leu genotypic men in order to lower the risk of lifestyle-related diseases.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have found that both SBP and DBP were lower in non-drinkers with ND2-237Leu than in those with ND2-237Met (7), and that serum uric acid levels were lower in non-obese non-daily drinkers with ND2-237Leu than in those with ND2-237Met (11). Only among men with ND2-237Leu, habitual drinking was reportedly and positively associated with intraocular pressure (21). Therefore, abstaining from alcohol consumption, or at least avoiding daily alcohol consumption, is particularly recommended for ND2-237Leu genotypic men in order to lower the risk of lifestyle-related diseases.…”
Section: Discussionmentioning
confidence: 92%
“…We previously reported that longevity-associated ND2-237 Leu/Met polymorphism modulates the effects of habitual alcohol drinking on blood pressure (7), serum triglyceride levels (9), serum uric acid levels (11) and intraocular pressure (21). Habitual alcohol consumption influences the production of ROS by NADH dehydrogenase (22), and modifies the susceptibility of mitochondrial proteins, including NADH dehydrogenase, to ROS (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have discovered gene-environment interactions between Mt5178 C/A polymorphism and smoking habits for serum triglyceride levels (Kokaze et al 2003a), intraocular pressure (Kokaze et al 2004b), hematological data (Kokaze et al 2005b), serum protein fraction levels (Kokaze et al 2003b), and, in this study, FEV 1 /FVC ratio. The precise mechanisms through which Mt5178 C/A polymorphism exerts its interaction with habitual smoking, and thereby affects biophysical and biochemical status, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the Mt5178A genotype, a genetic marker of mitochondrial haplogroup D, is significantly higher in Japanese centenarians than in the general population (Alexe et al 2007;Tanaka et al 1998) and it is reported that individuals with Mt5178A (mitochondrial haplogroup D) are less susceptible to lifestyle-related adult-onset diseases, for example hypertension (Kokaze et al 2007), diabetes (Wang et al 2001), metabolic syndrome ), myocardial infarction (Mukae et al 2003;Takagi et al 2004), and cerebrovascular diseases (Ohkubo et al 2002), than those with Mt5178C. Mt5178 C/A polymorphism is, moreover, also reported to be associated with blood pressure (Kokaze et al 2004a(Kokaze et al , 2007, serum lipid levels (Kokaze et al 2001(Kokaze et al , 2003a, fasting plasma glucose levels and glucose tolerance (Kokaze et al 2005a), serum uric acid levels (Kokaze et al 2006), intraocular pressure (Kokaze et al 2004b), hematological data (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2002(Kokaze et al , 2003b, and its interaction with smoking habits is associated with serum triglyceride levels (Kokaze et al 2003a), intraocular pressure (Kokaze et al 2004b), red blood cell counts (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2003b). As far as we are aware, however, no information is available about the relationship between Mt5178 C/A polymorphism and respiratory function or about its interaction with smoking habits in respiratory function.…”
Section: Introductionmentioning
confidence: 99%